2015
DOI: 10.1038/bmt.2015.10
|View full text |Cite
|
Sign up to set email alerts
|

5-Azacytidine and DLI can induce long-term remissions in AML patients relapsed after allograft

Abstract: DNA-hypomethylating agents are a viable treatment option for AML/myelodysplastic syndrome (MDS) relapse after allograft by upregulating Ags on blasts before DLI. Seventy-two patients with relapsed AML (n = 62), MDS (n = 8) and other myeloid neoplasms (n = 2) after allograft were treated with low-dose 5-azacytidine and, if feasible, DLI. Patient characteristics: median age 62 years (range 20-75), 42% with adverse cytogenetics, 82% not in remission at transplant and 83% received fludarabine-based reducedtoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 24 publications
3
55
0
2
Order By: Relevance
“…Newer relapse concepts implement hypomethylating agents such as 5-azacytidine before DLI infusion, resulting in promising long-term remission rates in a subset of patients. 17 However, preventing the occurrence of relapse should be the primary goal of future concepts. In this regard, several groups are investigating the role of 5-azacytidine as part of a maintenance treatment after allogeneic hematopoietic cell transplantation in high-risk AML patients as demethylating agents have been shown to increase the GvL effect while reducing GvHD.…”
Section: Discussionmentioning
confidence: 99%
“…Newer relapse concepts implement hypomethylating agents such as 5-azacytidine before DLI infusion, resulting in promising long-term remission rates in a subset of patients. 17 However, preventing the occurrence of relapse should be the primary goal of future concepts. In this regard, several groups are investigating the role of 5-azacytidine as part of a maintenance treatment after allogeneic hematopoietic cell transplantation in high-risk AML patients as demethylating agents have been shown to increase the GvL effect while reducing GvHD.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the publications regarding the use of Aza as salvage treatment for relapse after allo-SCT: until now a total of 601 patients with AML, MDS and other related myeloid malignancies have been published with varying schedules and dosages of Aza. These included 3 prospective, non-randomized trials and the majority of patients reported retrospectively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Furthermore, Aza was the first treatment of relapse and combined with DLI in some of these patients, while other patients had previously received other salvage therapies or did not receive DLI.…”
Section: Azacitidine For the Treatment Of Relapsementioning
confidence: 99%
“…8 Donor lymphocyte infusion (DLI) can result in prolonged CR but only in a minority of patients with low-disease burden. 9 Similarly, an association of DLI and azacitidine induces only a few persistent CR, 10 whereas a second allo-HCT (in a group of highly selected patients) results in a 2-year OS rate of 20%. 11,12 Given the poor prognosis of patients who experience relapse after allo-HCT, several groups of investigators have assessed various post-transplant approaches aimed at preventing disease relapse in high-risk AML patients (Table 1).…”
mentioning
confidence: 99%